Lactic Acid Bacteria That Produce Antibacterial Compunds on Candied Pakoba Fruit Syzygium luzonense - Runtuwene, Kharly; Lawalata, Helen; Posumah, Dany; Satiman, Utari; Moko, Emma (Universitas Negeri Manado, 2025)
Lactic Acid Bacteria (LAB) are a group of Gram-positive, cocci or rod-shaped microorganisms characterized by their catalase-negative phenotype. These bacteria are known to produce various antibacterial compounds, including organic acids, hydrogen peroxide, carbon dioxide, and bacteriocins, which exhibit bacteriostatic or bactericidal properties against pathogenic bacteria. The aim of this study is to isolate LAB that produce antibacterial compounds during the fermentation of Pakoba fruit (Syzygium luzonense) into sweets, with a focus on inhibiting the growth of Escherichia coli and Staphylococcus aureus. This research employs a quantitative descriptive method, involving the isolation of LAB from candied Pakoba fruit samples and subsequent testing of their antibacterial activity against the aforementioned pathogens. The barrier zone formed around the wells is then measured. The data from the study showed that BAL isolation from Pakoba fruit candied was obtained from as many as 10 isolates, and antibacterial activity tests showed that 10 BAL isolates produced antibacterial compounds with inhibitory diameters of 7.6 – 15.3 mm. The isolates with the greatest antibacterial activity are LAB isolate MP(1)5.2 for E. coli and LAB isolate MP(3)6.3 isolates for S. aureus. Based on the results of identification using the profile matching method, it was shown that the selected LAB isolates, namely MP(1)5.2 and MP(3)6.3, were classified in the genus Lactobacillus with the characteristics of stem cell shape, single cell arrangement, catalase-negative, non-motile, did not form spots, and did not produce gas from glucose.